Epoxy vitrimers: The effect of transesterification reactions on the network structure - Altuna, Facundo Ignacio (2018)
Vitrimers are covalently crosslinked polymers that behave as conventional thermosets below the glass transition temperature (Tg) but can flow above a particular temperature, Tv > Tg, by bond exchange reactions. In epoxy vitrimers, transesterification reactions are responsible for their behavior at T > Tv that enables flow, thermoforming, recycling, self-healing and stress relaxation. A statistical analysis based on the fragment approach was performed to analyze the evolution of the network structure of epoxy vitrimers during transesterification reactions. An analytical solution was obtained for a formulation based on a diepoxide and a dicarboxylic acid. A numerical solution was derived for the reaction of a diepoxide with a tricarboxylic acid, as an example of the way to apply the model to polyfunctional monomers. As transesterification acts as a disproportionation reaction that converts two linear fragments (monoesters) into a terminal fragment (glycol) and a branching fragment (diester), its effect on network structure is to increase the concentration of crosslinks and pendant chains while leaving a sol fraction. Changes in the network structure of the epoxy vitrimer can take place after their synthesis, during their use at high temperatures, a fact that has to be considered in their technological applications.